Anticipatory information sources in elite softball batting: A qualitative approach - Carboch, J.; Praveckova, P.; Joska, M. (Journal of Human Sport & Exercise, 2026)
Batting performance against high-speed pitches in softball requires effective anticipation skills. While these skills can vary individually, it remains unclear which anticipatory cues players rely on. The aim is to explore the anticipatory information sources and pitch-related cues perceived and considered by elite softball batters. We interviewed eight elite softball players (25 to 50 minutes each), and their responses were transcribed and analysed using an open-coding approach. Subsequently, the responses were thematically organized into higher and lower-order themes. Seven higher-order themes emerged: consciousness, contextual information sources, kinematic information sources, tactical awareness, mentality/confidence, batting technique and strategy, and skill acquisition/training. These themes highlight the various anticipatory information sources players use, as well as the role of kinematic and contextual cues in batting performance. Further analysis revealed detailed lower-order themes within each higher-order theme. A temporal model was developed to illustrate the sequence and interaction of both kinematic and contextual information sources that influence the anticipation skills of expert softball players.